BATTLES OF PANIPAT, SIKRI AND HAVNA (Academia Science Repository, 2023)
The article reveals the military art of the great king and poet Zahiruddin Muhammad Babur, especially the battles of Panipat and Sikri, the most important battles of his conquest of India, and the factors of their victory. The article also presents the opinions and comments of some Indian and European historians about these battles, and compares the sources.